Relationship Between Nurses' Innovative Behaviors and Organizational Creativity Levels - Aliye Güllübal; Tülay Sağkal Midilli (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This research aims to reveal whether there is a significant difference between nurses' innovation behaviors and organizational creativity levels according to demographic variables. Method: The research is descriptive and cross-sectional. The sample of the research conducted between September and November 2021 consisted of 280 nurses working in two public hospitals in Turkey. 'Nurse Introduction Form', 'Individual Innovativeness Scale' and 'Organizational Creativity Scale' were used to collect data. Research data were used in frequency analysis in the Statistical Package for Social Sciences (SPSS) 15.0 package program. Number percentage distribution, descriptive analysis, Mann-Whitney U, Kruskal-Wallis Test and Spearman correlation analysis were used to analyze the data. Results: In the study, the average score of the nurses' individual innovativeness scale was found to be 64.21 (SD=8.87). The mean organizational creativity scale of nurses was found to be moderate (Mean=2.95, SD=0.59). It was determined that there were positive, weak, and statistically significant relationships between nurses' individual innovativeness and organizational creativity levels. (p<0.05). Conclusion: It was determined that there were significant relationships between nurses' individual innovation and organizational creativity. It has been observed that as individual innovativeness characteristics increase positively, the level of organizational creativity increases. As a result of the descriptive tests and Spearman correlation analysis, it is important to evaluate and increase the innovation levels of nurses and the level of using their creativity in increasing innovative behaviors in nursing, encouraging undergraduate and graduate education, increasing psychological support, providing innovation-related training programs and management support for the development of nurses' creativity.